The Influence of Green Accounting and Carbon Emission Disclosure on Company Value - Bernadetta Ika Prasetyaningsih; Sutoyo Sutoyo; Sujatmika Sujatmika (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the era of globalization and increased awareness of the impacts of climate change, sustainable development has become one of the main concerns at the global level. One of them is the disclosure of carbon emission disclosure and the application of green accounting in the company's operational process as an effort to overcome environmental problems. This study aims to determine whether green accounting & carbon emission disclosure has a positive effect on firm value. The study uses secondary data obtained from annual reports and corporate sustainability reports for the 2019-2023 period. Companies with the energy sector listed on the Indonesia Stock Exchange in 2019-2023 are the criteria for this research data. Data processing using Statistical Package for Social Science. The results showed that the application of green accounting & carbon emission disclosure has no influence on firm value. The ineffectiveness of green accounting and carbon emission disclosure on firm value is likely due to the proxies used in this study that do not fully represent the true indicators of green accounting and carbon emission disclosure. Future research is recommended to use other proxies that are more relevant in measuring green accounting and disclosure of carbon emissions.